1995
DOI: 10.1021/ic00107a007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Oxygen Exchange and Inversion along the M:O Axis in the Diprotonated and Monoprotonated Dioxotetracyanometalate Complexes of Re(V), Tc(V), W(IV), and Mo(IV)

Abstract: Oxygen-17 NMR was utilized in aqueous medium (1.2-2.4 m KNO3) to study the oxygen exchange kinetics in the irans-dioxotetracyanometalate complexes of Re(V), Tc(V), W(IV), and Mo(IV). The kinetics are described by the two-term rate law R = (fcaq[MOH2] + &oh[MOH])/2, where MOH2 and MOH represent the diand monoprotonated forms, [MO(OH2)(CN)4]"~a nd [MO(OH)(CN)4](n+, |~, of the dioxotetracyanometalate complexes, respectively. The aqua complexes are by far more reactive toward exchange (kaq values of (9.1 ± 0.1) x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The bridging OH groups do not exchange with the bulk solvent, on the NMR time scale of these experiments. 17 O NMR was utilized to study the oxygen exchange kinetics in the trans-dioxotetracyanometalate complexes of Re(V), Tc(V), W(IV), and Mo(IV) [152]. The exchange rate data of the aqua-complexes are in agreement with a dissociative activation, whereas the exchange rate of the hydroxo complexes indicates a possible interchange/associative mechanism.…”
Section: Ionic Solvation: Diamagnetic and Paramagnetic Cationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The bridging OH groups do not exchange with the bulk solvent, on the NMR time scale of these experiments. 17 O NMR was utilized to study the oxygen exchange kinetics in the trans-dioxotetracyanometalate complexes of Re(V), Tc(V), W(IV), and Mo(IV) [152]. The exchange rate data of the aqua-complexes are in agreement with a dissociative activation, whereas the exchange rate of the hydroxo complexes indicates a possible interchange/associative mechanism.…”
Section: Ionic Solvation: Diamagnetic and Paramagnetic Cationsmentioning
confidence: 98%
“…As a result, a large number of experimental k, DH # , DS # and DV # values for many ions and different ligands have been derived [63,64,152,[596][597][598]747,795,796], which are listed in a number of tables in relevant reviews [807][808][809] where details of the experimental methods are also discussed.…”
Section: Ionic Solvation: Diamagnetic and Paramagnetic Cationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that, if the observation of 17 O NMR signals close to the water resonance is required, the presaturation experiment seems to be more successful compared with the 1-3-3-1 sequence [151]. The 1-3-3-1 pulse sequence was proven to be very effective in the suppression (by three order of magnitude) of the 17 O bulk water and the selective observation of bound water signal in oxygen exchange kinetic studies of complexes of W(IV) [152] (Fig. 22).…”
Section: Solvent (H 2 O) Suppressionmentioning
confidence: 99%
“…The substitution and protonation behavior of the dioxotetracyanometalate complexes of Re(V), Tc(V), W(IV), and Mo(IV) have been extensively investigated in the past decade and have recently been reviewed We have furthermore reported the characterization of these oxo complexes with NMR and were able to correlate chemical shifts and acid/base behavior with structural and infrared data. …”
Section: Introductionmentioning
confidence: 99%